Lubuk Tiara Sdn. Bhd. Miri, Sarawak - Ismail, Ahmad Suriadi (Universiti Teknologi MARA, Sarawak, 2016)
I have learned a lot of valuable things while working here. I realized that Seaming theoretical is never the same when it comes to practice. There are a lot more to master than just learning from book. For example it is impossible to master the etiquette of communicating with others from the book unless we put it in action. I also learned it is very important to know how to work as part of the team especially when you are working in a big organization. In order to complete the task given timing Is also another crucial thing to take care of. As is it known, the world of working is a completely different phase compared to the time when we are studying, therefore by going for an industrial training it is in hope that the students are well prepared and have high confidence to serve the community. Students have to carry a big responsibility when working at industry and carry it with honestly and sincerity.